Analisis Spasial Tuberkulosis Paru Ditinjau dari Faktor Demografi dan Tingkat Kesejahteraan Keluarga di Wilayah Pesisir - Nafsi, Anisa Yulia; Rahayu, Sri Ratna (Jurusan Ilmu Kesehatan Masyarakat, Fakultas Ilmu Keolahragaan, Universitas Negeri Semarang, Indonesia, 2020)
The number of new cases of positive BTA tuberculosis in the working area of ​​the Puskesmas Bandarharjo was the highest in Semarang City in 2018 with 46 cases (IR = 12 / 10,000 population), an increase from the previous year which was 43 cases. The purpose of this study was to analyze the incidence of pulmonary TB spatially in terms of demographic factors (age, gender, population density and house density) and the level of family welfare in the working area of ​​ Puskesmas Bandarharjo in 2018. This research is a quantative descriptive with cross sectional study. Data analysis used univariate analysis and spatial analysis. The results of spatial analysis showed that as many as 65.22% of cases were male. More cases occurred at productive age as much as 86.96%. There are 69.6% found in areas with low population density and 30.4% in areas with high population density. As many as 100% of cases are in areas with high housing density. The highest level of underprivileged families is in Dadapsari Urban Village as much as 25.89%. Keywords : Spatial Analysis, Pulmonary TB, Demographic Factors, Family Welfare Level.